Acidity index of different buriti oil samples subjected to spectroscopy in infrared region and principal component analysis - Braian Saimon Frota da Silva; Bruno Willams Maciel Batista; Kevin Lucas Soares Costa; Cláudio Nahum Alves; Simone de Fátima Pinheiro Pereira; Nelson Rosa Ferreira (Pesquisa Agropecuária Brasileira)
Abstract The objective of this work was to evaluate the use of chemometric tools associated with mid-infrared waves (ATR-MIR-FTIR) to determine the acidity index (AI) of Mauritia flexuosa oil extracted from plants from different locations. Thirty oil samples were collected in five municipalities of the state of Pará, Brazil. The principal component analysis, combined with Hotelling’s T² multivariate control test, was used to identify anomalous samples from the spectra. The ATR-MIR-FTIR analysis showed that the oil contains mainly monounsaturated acids, including oleic acid, which is directly correlated with AI. The first two principal components explained 99.93% of the cumulative variance. The statistical methods identified patterns of similarities between the samples with a close AI and tested an outlier from the sample with the highest AI. The application of ATR-MIR-FTIR, associated with chemometric methods, is appropriate to evaluate the acidity of buriti palm oil samples.